Spectrophotometric Determination of Irinotecan in Pharmaceutical Formulations - Murali Balaram, V.; Venkateswara Rao, J. (Asian Journal of Chemistry, 2010)
A new simple, sensitive and cost effective visible spectrophotometric method was developed for the estimation of irinotecan in both bulk drug samples and injections. The method was based on the formation of ion pair complexes of the drug with two acidic dyes namely bromocresol green and bromophenol blue in acidic buffer solution followed by their extraction in organic solvent (chloroform).The absorbance of the organic layer was measured at their respective absorption maxima at 420 nm for bromocresol green and 380 nm for bromophenol blue against the corresponding reagent blank. The method obeyed Beer's law between 3.0-37.5 μg/mL for bromocresol green and 1.0-12.5 μg/mL for bromophenol blue.The results of recovery experiments indicated average recovery was above 99.86 % and using the t-statistic, hypothesis was tested for the correlation between the amount added and amount found, at a confidence level of 0.05 (5 %). It was proved that there was a strong correlation between the amount added and amount found. The interference studies also revealed the common excipients and other additives usually present in pharmaceutical dosage forms did not interfere in the proposed method.The proposed method is precise, accurate, sensitive and cost effective and can be used in routine analysis in quality control laboratories.